Company Responsibility Towards Community Affected by Palm Oil Waste Perspective of Maqashid Sharia (PT Karya Agung Sawita in Padang Lawas Regency) - Nasution, Wina Syafitri; Hasanah, Uswatun (AL-IKTISAB: Journal of Islamic Economic Law, 2023)
Palm oil waste is the residue produced from the palm oil processing process, which has the potential to cause environmental pollution, and palm oil waste is also one of the main environmental issues in Indonesia that significantly impacts public health and the surrounding ecosystem. Palm oil waste can also cause damage to the environment around the company, therefore, it is essential for the company to take responsibility by ensuring the safety and health of the community living near the company. The purpose of this research is to understand the form of corporate responsibility towards the surrounding community affected by palm oil waste at PT Karya Agung Sawita located in Padang Lawas regency, and to examine the maqashid sharia perspective on the community affected by the company's palm oil waste. The research method used in this research is qualitative with an empirical juridical approach sourced from interviews. The results of this research found that the company's form of responsibility includes waste management into palm oil fertilizer, corporate social responsibility, providing bore wells, providing clean water ponds, compensation and recovery, and internal supervision and sanctions. And the form of corporate responsibility is also not yet fully aligned with maqashid sharia, especially on the points of hifzd nafs (preserving life), hifzd mal (preserving wealth), hifzd nasl (preserving lineage), and hifdz aql (preserving intellect). Therefore, the company can provide benefits to the community if it has fulfilled its responsibilities well, because palm oil waste can cause harm and eliminate dharuriyat al-khamsah if not properly managed, bringing goodness and avoiding harm, which aligns with the objectives of sharia or the goals of maqashid sharia in establishing laws.